Minicontos multimodais a partir de tiras da Turma da Mônica - Santos, Tânia Andrade Oliveira (2015)
New textual genres added a variety of semiotic resources were put into circulation with technological innovations, requiring readers and producers of texts the development of multiliteracies. The school should provide urgently its students the study of these digital genres, preparing its students to deal with this new reality. Aware of this scenario, this report is intended to present the results of the first application of the Pedagogical Notebook entitled Producing multimodal minicontos from strips Monica´s Gang performed in a 7th class year. This notebook was structured theoretical and methodologically from the Cosson model (2006) there is a didactic sequence (SD) constituted of the following steps: motivation, introduction, reading and interpretation, and also the Dolz of SD model, Noverraz and Schneuwly (2004), for which a SD presents initial production, divided activities into modules and final production. Writers such as, Marcuschi (2008; 2010), for which genres are changeable, plastic sociodiscursivas entities; Kress and Van Leeuwen (2001) that deals with multimodal speech; Dionysus (2011), which deals with multimodal genres and multiletramento; Roxane Rojo (2012), with her work on multiliteracies in school; Lemke (2010), which deals with the metamidiatico multiletramento; Passarelli (2012), with her study of the text production in the classroom, from the emphasis on the idea that it should be worked as a procedural activity and Suassuna (2011), which discusses the importance of the teacher as mediator in the process assessment and rewriting the text, gain prominence in this technical support. For application, the class was divided into groups, since the exchange with each other the subject can be developed, and also for not having enough computers for the work to be individual. The first application of this analysis showed a positive result, as which was possible to observe a substantial improvement between the first and last version produced. Similarly, students were able to handle technological tools and a variety of semiotic resources for the production of multimodal minicontos, expanding their skills. In addition, this Pedagogical Notebook allows other teachers resignify the text production in the classroom and expand the interactive competence of their students.